2001
DOI: 10.1111/j.1479-828x.2001.tb01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there an interaction between cervical length and cervical microbiology in the pathogenesis of preterm labour?

Abstract: Transvaginal ultrasound of the cervix is increasingly used to estimate cervical length during pregnancy. Initially used to determine a possible need for cervical suture, the technique has been shown to be of value in the prediction of preterm delivery In addition, bacterial vaginosis has been shown to be associated with an increased risk of preterm delivery. We hypothesised that shortening of the cervix and potential cervical pathogens, in particular the presence of bacterial vaginosis, act synergistically in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…In a prospective follow‐up study of 316 women between 18 and 28 weeks' gestation a strong correlation was found between a shortened cervix and preterm delivery at 18 weeks' gestation, especially if the woman also has cervical pathogens (111). Cervical length <20–15 mm at 23–24 weeks' gestation is reported to be associated with increased risk of preterm birth (109,112).…”
Section: Measurement Of Cervical Lengthmentioning
confidence: 99%
“…In a prospective follow‐up study of 316 women between 18 and 28 weeks' gestation a strong correlation was found between a shortened cervix and preterm delivery at 18 weeks' gestation, especially if the woman also has cervical pathogens (111). Cervical length <20–15 mm at 23–24 weeks' gestation is reported to be associated with increased risk of preterm birth (109,112).…”
Section: Measurement Of Cervical Lengthmentioning
confidence: 99%
“…125 Further, women with a short cervix and bacterial vaginosis have a significantly higher risk of preterm delivery than women with just one of these risk factors. 162 The interaction between cervical and infective risk factors would be anticipated to be highest prior to chorio-decidual fusion. During later pregnancy this factor could differentially affect the dependent memberanes and induce the local mechanism associated with term LROM.…”
Section: Cervical 'Incompetence'mentioning
confidence: 99%
“…In a prospective follow-up study of 316 women between 18 and 28 weeks' gestation a strong correlation was found between a shortened cervix and preterm delivery at 18 weeks' gestation, especially if the woman also has cervical pathogens (111). Cervical length <20-15 mm at 23-24 weeks' gestation is reported to be associated with increased risk of preterm birth (109,112).…”
Section: Measurement Of Cervical Lengthmentioning
confidence: 99%